PENGARUH STRATEGI PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH DASAR NEGERI 1 BIREM KABUPATEN ACEH TIMUR - Husniah Husniah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The objectives of this research were to find out: (1) the different effect betweeninductive and deductive instructional strategy toward Islamic Education achievement,(2) the difference of the Islamic Education achievement between student with highlearning motivation and low learning motivation, and (3) the interaction betweeninstructional strategy and learning motivation toward Islamic Education achievement.The population of this research was all students of Grade V V SDN 1 Birem consistingof two classes. The sampling technique applied was cluster random sampling taughtwith inductive instructional strategy and the students taught with deductiveinstructional strategy. The instrument used to measure the Islamic Educationachievement was a multiple choice test. The instrument used to measure the students’learning motivation was questionnaire. The normality test used Liliefors and thehomogeneity test was Fisher test and Bartlett test. The data analysis technique wasAnalysis of Variance with two-way at the level of significance  = 0,05 followed byScheffe test. The research findings were: (1) on average the students’ IslamicEducation achievement taught with inductive instructional strategy was X = 28.14which was higher than the average the students’ Islamic Education achievementtaught with deductive instructional strategy, which was X = 27.07 with F count = 35.08> Ftable = 3.96, (2) on average the student’ Islamic Education achievement with highlearning motivatione was X = 29.91, which was higher than the student’ IslamicEducation achievement with low learning motivation was X = 26.05 with F count = 4.28> F table = 3.96, and (3) there was an interaction between instructional strategy andlearning motivation toward Islamic Education achievement with F count = 9,94 > Ftable= 3.96.